Diagnosis of pulmonary hypertension from radiographic estimates of pulmonary arterial size. Issue 2 (February 1988) - Bush, A; Gray, H; Denison, D M
Abstract : The reported accuracy of radiographic measurements in predicting pulmonary hypertension is very variable. Measurements of right and left descending pulmonary artery diameter have been reported to provide a correct diagnosis in as many as 98% of patients. A study was carried out to determine the predictive value of measurements made from the chest radiographs of 50 normal subjects and of 27 patients undergoing right heart catheterisation for cardiac or pulmonary vascular disease, taking account of radiographic magnification. After such corrections a right descending pulmonary artery diameter over 16.7 mm or a left descending pulmonary artery diameter of over 16.9 mm distinguished 12 of 23 pulmonary hypertensive subjects, with no false positive results. The diameter was then arbitrarily squared (any differences between patients and control subjects being exaggerated) and the product was divided by either predicted or actual lung volume in an attempt to correct for body size. The new index distinguished 19 of 23 patients with pulmonary hypertension, with one false positive, when the divisor was actual lung volume; when predicted lung volume was used 18 of 23 patients were distinguished, again with one false positive result.